PENERAPAN MODEL PEMBELAJARAN INKUIRI DALAM PEMBELAJARAN MENULIS TEKS NEGOSIASI DI SMA - Septi Dilla Safitri; Yusra D.; Nurfadilah Nurfadilah (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the application of the inquiry learning model to learning to write negotiation texts in high school. This research is a descriptive qualitative research with qualitative data. The research data sources are divided into primary data and secondary data. The data collection techniques in this research are observation, interview, and documentation. The research data validity test uses the credibility test by triangulation. The data analysis technique of this research involves processing and preparing data, reading the entire data, starting data coding, applying the coding process to describe the things that are analyzed, showing descriptions and themes in qualitative narratives or reports, and interpreting the data. The results of this study show that the application of the inquiry learning model in learning to write negotiation texts includes planning, implementation, and assessment stages. The planning stage is related to the preparation of teaching modules. The implementation stage includes introduction, core, and closing activities. The assessment stage includes cognitive, affective, and psychomotor aspects.